2016
DOI: 10.1200/jco.2016.67.1222
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Longitudinal Analysis of 2-Hydroxyglutarate Magnetic Resonance Spectroscopy Identifies Broad Clinical Utility for the Management of Patients With IDH-Mutant Glioma

Abstract: Proton magnetic resonance spectroscopy (MRS) of the brain can detect 2-hydroxyglutarate (2HG), the oncometabolite produced in neoplasms harboring a mutation in the gene coding for isocitrate dehydrogenase (IDH ). We conducted a prospective longitudinal imaging study to determine whether quantitative assessment of 2HG by MRS could serve as a noninvasive clinical imaging biomarker for IDH-mutated gliomas. Patients and Methods2HG MRS was performed in 136 patients using point-resolved spectroscopy at 3 T in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 17 publications
6
137
1
1
Order By: Relevance
“…Several 2HG‐edited MRS methods have been proposed to increase the specificity of 2HG detection by MRS . Some of these methods have been evaluated in larger studies that demonstrated that specificity and sensitivity vary according to institution . In the study by de la Fuente et al, detection of 2HG by MRS depended on the tumor size (91% true‐positive rate for tumors measuring >8 cm 3 ), and in the studies by Choi et al and Jafari‐Khouzani et al, a conservative threshold of >1 mM was found to classify gliomas as having mutant IDH .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several 2HG‐edited MRS methods have been proposed to increase the specificity of 2HG detection by MRS . Some of these methods have been evaluated in larger studies that demonstrated that specificity and sensitivity vary according to institution . In the study by de la Fuente et al, detection of 2HG by MRS depended on the tumor size (91% true‐positive rate for tumors measuring >8 cm 3 ), and in the studies by Choi et al and Jafari‐Khouzani et al, a conservative threshold of >1 mM was found to classify gliomas as having mutant IDH .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods have been evaluated in larger studies that demonstrated that specificity and sensitivity vary according to institution . In the study by de la Fuente et al, detection of 2HG by MRS depended on the tumor size (91% true‐positive rate for tumors measuring >8 cm 3 ), and in the studies by Choi et al and Jafari‐Khouzani et al, a conservative threshold of >1 mM was found to classify gliomas as having mutant IDH . However, the sensitivity of MSR is not solely dictated by the tumor size, but by the density of mutant IDH cells and the efficiency of 2HG production.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers reported imaging of 2HG in patients with IDH‐mutant gliomas at 3T. In two Choi et al studies that used 2D phase‐encoded CSI with 10 × 10 × 15 mm 3 (1.5 mL) voxel size, the volumes with elevated 2HG were about the same as those with T 2 w‐FLAIR hyperintensity. Using a 3D spiral imaging method with 20 × 20 × 20 mm 3 voxel size (8 mL), Jafari‐Khouzani et al reported larger volumes with elevated 2HG than T 2 w‐FLAIR volumes and partial agreement on the locations of the 2 volumes in more than half of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study of 136 patients followed 2‐HG levels over repeated scans throughout treatment. Using a cutoff of 1 mM 2‐HG, the authors reported 100% sensitivity and 88% specificity for IDH mutation subsequently confirmed by histology, and of patients who were unable to undergo resection, a molecular diagnosis could be established in 67% by MRS. Impressively, the authors were able to measure a rapid increase in 2‐HG concentration in tumors under observation at the time of their progression . Therefore, clinicians may find it useful to track 2‐HG levels in low‐grade gliomas under observation, to identify progression even in the absence of classic features on standard MRI.…”
Section: Introductionmentioning
confidence: 99%